International Conference "Contentious Collections in Central and Eastern Europe: The Legacy of Ethnographic Shows and Beyond", 26–27 October 2023, Institute of Latvian History, University of Latvia - (:unkn) unknown (University of Latvia, 2023)
Researchers in history, cultural heritage studies, ethnography and anthropology, art and museology, at different stages of their career are gathered in Riga for the international conference co-organized by the Institute of Latvian History, University of Latvia and the Institute of Archaeology and Ethnology, Polish Academy of Sciences. Two keynote lectures and 23 presentations address concerns about various types of contentious collections: virtual, private, museum, university, etc. For the purpose of the conference, contentious collections are defined as groups of non-European objects that were purchased and incorporated into Central and Eastern European collections in the 19th and 20th century, in which the themes of Otherness, savagery, primitivism, exoticism, and racism played a significant role. The complex history of contentious collections, together with the contemporary entanglements of their status, perception, and interpretation, are the main topics of conference presentations discussed from a comparative, interregional, and dialogical standpoint. The conference is organized with the support of the Academic Development Project of the University of Latvia and the financial assistance of the Institute of Archeology and Ethnology of the Polish Academy of Sciences.

LU Latvijas vēstures institūta un Polijas Zinātņu akadēmijas Arheoloģijas un etnoloģijas institūta kopīgi organizētā starptautiskā konference vieno vēstures, kultūras mantojuma, etnogrāfijas un antropoloģijas, mākslas un muzeoloģijas pētniekus dažādos karjeras posmos. Konferences divās ievadlekcijās un 23 referātos aktualizēti ar strīdīgajām virtuālajām, privātajām, muzeju, universitāšu kolekcijām saistīti jautājumi. Konferences izpratnē diskutablās kolekcijas ir ārpus Eiropas izcelsmes priekšmetu grupas, kas iegūtas un iekļautas Centrāleiropas un Austrumeiropas kolekcijās 19. un 20. gadsimtā, un glabā priekšmetus, kas atbilst tādām tēmām kā citādība, primitīvisms un rasisms. Konferences fokusā atrodas strīdīgo kolekciju sarežģītā vēsture, tai skaitā to statusa, uztveres un interpretācijas samezglojumi mūsdienās salīdzinošā, starpreģionālā un dialogikas perspektīvā. Konferences norisi nodrošināja LU Akadēmiskās attīstības projekts “Starptautiska, starpdisciplināra zinātniska konference “Contentious Collections in Central and Eastern Europe: The Legacy of Ethnographic Shows and Beyond”” ar Polijas ZA Arheoloģijas un etnoloģijas institūta finansiālu atbalstu.
Starptautiska konference "Diskutablās kolekcijas Centrālajā un Austrumeiropā: koloniālisma un eksotisko etnogrāfisko izrāžu mantojums" 2023. gada 26.–27. oktobris, LU Latvijas vēstures institūts
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects; contentious collections; ethnic / ethnographic shows; legacy; non-European objects; (post)colonialism; Central and Eastern Europe; diskutablās kolekcijas; etniskās / etnogrāfiskās izrādes; mantojums; ārpus Eiropas izcelsmes objekti; (post)koloniālisms; Centrāleiropa un Austrumeiropa